Tuning Fuzzy Membership Functions To Improve Performance Of Vector Control Induction Motor Drives - Zulhisyam, Salleh; Marizan, Sulaiman; Rosli, Omar (Penerbit Universiti, UTeM, 2016)
This paper presents an effective strategy for tuning of fuzzy membership functions based on fuzzy logic controller approach for a vector controlled induction motor drives for high performance applications. Initially, the input scaling factors are calculated based on known motor data and symmetrical triangular membership functions have been used for standard design. Then, asymmetrical convergent peak value positions of these membership functions have been considered to improve the control performance. The simulation test is done for low, half and full rated speed response and load disturbance for full rated speed. By tuned membership functions, the results demonstrate that the robustness and the effectiveness of fuzzy logic controller for high performance of induction motor drives system is achieved.